FARMER"™S ORGANIZATION, MANAGEMENT AND SUSTAINABLE IMPROVEMENT OF INDEPENDENT PALM OILFARMER"™S TOWARD ECONOMIC BENEFITS - Egi, Kosmas; Nurliza, Nurliza; Kurniati, Dewi (Jurnal Sains Pertanian Equator, 2019)
ABSTRACT Economic benefits as a reference in measuring the physical level of independent smallholders as a result of palm oil farmer"™s. independent farm that are measured through the organizational aspects of planters and farm management and sustainable business enhancements lead to pros and cons of the situation in the field. These problems lead to the need to conduct research on independent farm in order to have knowledge and responsibility for economic sustainability. The purpose of the study was to analyze the influence of planters' organizations and farm management and the sustainable improvement of business to economic benefits, in 150 respondents who were selected purposively. Data analysis using Structural Equation Modelling (SEM). The results showed that the organizational factors of planters and garden management had no effect. However, the attributes of sustainable business improvement are the most important factors in economic benefits followed by post-harvest increases. Keywords: Economic benefits, Farmer"™s organizations, Management, Sustainable improvement, Structural Equation Modeling (SEM).